Proveniência e contexto digital : contribuições da ciência da informação - Arakaki, Felipe Augusto (Palabra Clave.)
The objective of this article is to discuss the concept of provenance and highlight its importance in the digital environment, focusing on the perspective of Information Science. As methodological procedures, it was characterized by being a qualitative and exploratory research, from a literature review on the context of provenance in different domains. The article presents a discussion of the term provenance in several contexts, such as in Achival Science, Museology, Digital Preservation and Computing, highlighting its importance in the digital sphere. As discussed the relevance of provenance in different contexts, the need for more in-depth studies is highlighted, analyzing whether the instruments to represent provenance are adequate to guarantee the veracity and inalterability of the information. Thus, the discussions exposed in this article reveal possibilities in identifying metadata for each characteristic that the provenance may present, in addition to the feasibility of expansion to other contexts.